Expediente Espaço em Revista - Pires , Ana Paula Novais Pires; Silva, Juniele Martins; Reis, Bruno Serafim dos; Silva, Laira Cristina; Matos, Patrícia Francisca; Nazar, Thallita Isabela Silva Martins (Espaço em Revista, 2022)
Expediente Espaço em Revista, v. 23, n. 2, jul./dez. 2021.